Behavioural Factors Influencing Investment Decisions and Performance in the Nepal Stock Market - Timalsina, Saujanya; Lama, Pranam; Bhandari, Kapil (Journal of Multidisciplinary Research Advancements, 2026)
This study investigates the influence of behavioural factors on the investment decisions and perceived performance of individual investors in the Nepal Stock Exchange (NEPSE). Grounded in behavioural finance theory, the research examines the impact of four key factors: Heuristic biases (overconfidence, anchoring), Prospect Theory elements (loss aversion, regret aversion), Market factors (information, trends, fundamentals), and Herding behaviour. Utilising a quantitative research design, data were collected via a structured questionnaire from 120 active individual investors in Kathmandu. The data were analysed using descriptive statistics, correlation, and multiple regression analysis. The findings reveal that Herding behavior and attention to Market factors are the most significant and positive predictors of investors’ self-assessed investment performance. In contrast, Heuristic and Prospect variables showed no statistically significant impact. Furthermore, investment performance did not vary significantly across demographic groups, including gender, age, or education. The results underscore the dominant role of social influence and collective market analysis over individual cognitive biases in the context of an emerging market like Nepal. The study contributes to the behavioural finance literature by highlighting the context-specific hierarchy of behavioural influences. It offers practical implications for investors, financial advisors, and market regulators in developing economies.